NEWBORNS OF HIGH RISK GROUPS AND ELECTROPHYSIOLOGICAL CARDIAC ACTIVITY DURING THE PERIOD OF EARLY ADAPTATION - T. S. Tumaeva; L. A. Balykova (Вопросы современной педиатрии, 2014)
Aim: to study characteristics of electrophysiological cardiac activity in children of risk groups and to assess possibilities of Holter-electrocardiography (H-ECG) in revealing of cardiac dysfunction during the period of early adaptation. Patients and methods: 250 newborns were examined. The main group consisted of 200 children with cerebral ischemia (CI). This group was divided into 2 subgroups: 100 full-term and 100 premature (at various gestation age) infants. Control group contained 50 children born at 38–40th weeks of gestation with physiological course of pregnancy and delivery, APGAR score of 8–9 points. Complex examination included H-ECG according the standard technic with evaluation of the hearth rate (HR) during sleep and wakefulness; HRmin, HRmax; arrhythmias, conductivity disorders, duration of the intervals; rhythm variability. Results: according to the ECG children with CI, especially premature ones, and children delivered via Cesarean section more often had ST-T disturbances, arrhythmias (sinus tachycardia, less often — sinus bradycardia) and conductivity disorders, Q-Tc prolongation. H-EGC revealed decrease of sleep HR, HRmin and HRmax in children with CI especially in delivered via Cesarean section. The most common arrhythmia was supraventricular extrasystole.  Pauses in rhythms and variability were the highest in premature children delivered via Cesarean section. Conclusions: hypoxia/ischemia is a trigger for development of cardiovascular dysfuncion in newborns. Premature and children delivered via Cesarean section form a group of high risk. H-ECG widens possibilities of revealing of symptoms of cardiac dysfunction (disturbances at the basal level of functioning, of adaptation resources of the sinus node, electric instability of the myocardium and heart rate variability) in children of risk group for development of cardiovascular disorders.